LAUNCHING DAN PELATIHAN PENERAPAN WEBSITE DESA PAGELARAN - Muhamad Muslihudin (LP3K Lampung, 2021)
The village is an area occupied by a number of residents as a community unit in which there is a legal entity that has the lowest government organization directly under the sub-district head and is not entitled to run its own household. Pagelaran Village is a village located in Pagelaran District, Pringsewu Regency. Pagelaran Village is located in the west of Pringsewu Regency. With a land area of ​​326.6 ha and has a population of 5,601 people. Information about the village is important to provide information to the community. For the community, information about the village is usually obtained when there are village activities. The above problems can be solved by having a village website where this website contains a village profile containing data from the Pagelaran Village, the latest information, and correspondence in the Pagelaran Village.